Soil, plant, water, fertilizer, animal manure and compost analysis manual - Tadesse, T.; Haque, I.; Aduayi, E.A. (International Livestock Centre for Africa, 1991)
Describes procedures for the analysis of chemical constituents in soil, plant, water, fertilizer, animal manure and compost samples. Includes simple procedures for collecting, preparing and storing samples, including information on the need to care for field and laboratory materials such as sampling tools, glasswares and other general precautions required for adequate and reliable analytical results. The procedures include organic matter, total and available nitrogen & phosphorus, exchangable cations, cation exchange capacity, micronutrient elements, exchangable aluminium, lime requirement, gypsum content in soil, plant and water analysis for mineral nutrients and moisture in fertilizers, animal manure and compost.